2007
DOI: 10.4049/jimmunol.179.11.7751
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA Mediates Bacterial Translocation to Dendritic Cells in Mouse Peyer’s Patches with Restriction to Mucosal Compartment

Abstract: In addition to fulfilling its function of immune exclusion at mucosal surfaces, secretory IgA (SIgA) Ab exhibits the striking feature to adhere selectively to M cells in the mouse and human intestinal Peyer’s patches (PPs). Subsequent uptake drives the SIgA Ab to dendritic cells (DCs), which become partially activated. Using freshly isolated mouse DCs, we found that the interaction with SIgA was tissue and DC subtype dependent. Only DCs isolated from PPs and mesenteric lymph nodes interacted with the Ab. CD11c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 59 publications
4
129
0
1
Order By: Relevance
“…27,28 In addition, IgA is the most abundant immunoglobulin in mucosal immunity 29,30 and it has been reported that IgA levels in the intestinal mucosa in acute liver necrosis patients were decreased significantly, but the mechanisms are not well understood. 31 Based on these studies and our new findings, we hypothesize that the liver may provide immunoprotection for the biliary tract and the intestines through secreting IgG and IgA into the bile and subsequently into the gut.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In addition, IgA is the most abundant immunoglobulin in mucosal immunity 29,30 and it has been reported that IgA levels in the intestinal mucosa in acute liver necrosis patients were decreased significantly, but the mechanisms are not well understood. 31 Based on these studies and our new findings, we hypothesize that the liver may provide immunoprotection for the biliary tract and the intestines through secreting IgG and IgA into the bile and subsequently into the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Commensal coating by colostrum-derived SIgA would translate into controlled primary gut colonization and the early education of the newborn immune system toward novel antigens prone to become symbiotic partners. We propose that coating of commensals by SIgA adds to the function of mucosal SIgA in maintaining gut homeostasis, and this process integrates potentiation of binding to epithelial cells (28), presentation under noninflammatory conditions (26), and luminal sequestration or limited penetration of host tissues (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…We reported in a previous study that IgA-based IC are taken up by intestinal M cells in Peyer's patches (20). Although the receptor(s) involved is (are) in need of identification, the phenomenon is specific for the IgA isotype (mouse IgA and human IgA2 only) and requires both the Fc␣1 and Fc␣2 domains of the Ab (7).…”
Section: Discussionmentioning
confidence: 99%
“…60 ng of purified rotavirus was incubated with 100 ng of either pIgA7D9 or SIgA7D9 in PBS for 2 h at room temperature, corresponding to ϳ160 Ab molecules/virus (19). 10 8 S. flexneri were incubated with 120 ng of either pIgAC5 or SIgAC5 in PBS for 25 min on ice, corresponding to ϳ2000 Ab molecules/bacterium (20). These conditions guarantee that no free pIgA/SIgA are found in the IC preparations.…”
Section: Methodsmentioning
confidence: 99%